Risk Factors for Progression or Malignancy in Main-Duct and Mixed-Type Intraductal Papillary Mucinous Neoplasm of the Pancreas. Issue 7 (August 2016) - Jang, Dong Kee; Ryu, Ji Kon; Chung, Kwang Hyun; Lee, Ban Seok; Park, Joo Kyung; Lee, Sang Hyub; Kim, Yong-Tae
Abstract : Objectives: The 2012 international guidelines state that surgery should be considered for all surgically fit patients with pancreatic main-duct (MD)/mixed intraductal papillary mucinous neoplasms (IPMNs). This study evaluated the follow-up results of MD/mixed IPMNs and risk factors for progression or malignancy. Methods: Patients with MD/mixed IPMNs were retrospectively enrolled and divided into surgical and nonsurgical groups. These 2 groups were compared and further categorized as progression/malignancy or not. In the nonsurgical group, disease progression was defined as radiologic tumor growth or adjacent organ invasion. Results: Data from 101 patients (73 males; mean [SD] age, 66.3 [9.1] years), including 27 and 74 in the nonsurgical and surgical groups, respectively, were analyzed. Mural nodules were more frequently detected in the surgical group (7.4% vs 31.1%, P = 0.018), whereas more multifocal cysts were observed in the nonsurgical group (40.7% vs 20.3%, P = 0.037). Forty-one patients (40.6%) showed progression or malignancy. Multivariate analysis showed that main pancreatic duct of 10 mm or greater (odds ratio, 4.368; P = 0.024) and pre-existing diabetes (odds ratio, 3.077; P = 0.046) were independent risk factors for progression or malignancy. Conclusions: A watchful waiting strategy could be feasible for some patients with MD/mixed IPMNs, particularly those with a main pancreatic duct of less than 10 mm and without diabetes.